Buddha Sasana Dan Hamemayu Hayuning Bawana Dalam Konteks Masyarakat 5.0 - wardani, Niken; Johny (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
This article examines how the values of the Buddhist Sasana and the Javanese philosophy of "Hamemayu Hayuning Bawana" can provide ethical and spiritual contributions in responding to the challenges of the Society 5.0 era. A qualitative approach with a desk study method is used to explore the integration of Buddhist moral values and cultural locality in building a humane, inclusive, and sustainable society. The results of the study indicate that Buddhist principles such as sila, mindfulness, and sustainability, as well as Javanese philosophy that emphasizes cosmic harmony and social responsibility, have high relevance in forming a super-intelligent society oriented towards humanity. This article recommends mainstreaming ethical values in education and technology policy.